EDUCATIONAL CRIMINAL SYSTEMS FOR CHILDREN AS A CRIMINAL ACTOR - Wulandari, Diah AYu (Universitas Negeri Semarang (UNNES), 2018)
Children are part of the community, they have the same rights as other communities to be protected and respected. Any State anywhere in the world is obliged to give adequate attention and protection to the rights of the child, which include civil, economic, social and cultural rights. However, it seems that the status and rights of the children when viewed from a juridical perspective have not received serious attention either by the government, law enforcers or the public in general and are still far from what should be given to them. This condition is compounded by the weak implementation of the law on the rights of the child committed by law enforcement officers themselves. The rights of the child shall be respected by everyone. One of them is in the punishment system which until now sometimes still treats the children involved as perpetrators of such crimes as perpetrators of criminal acts committed by adults. The child is placed in a position as a criminal offender who deserves the same punishment as an adult and applies in Indonesia. Whereas punishment itself is more oriented to individual perpetrators or commonly referred to as individual responsibility (personal Individual Responsibility) where perpetrators are viewed as individuals who are able to take full responsibility for the deeds it undertakes. While the child is an individual who has not been able to fully realize the actions / actions that he did, this is because the child is an immature individual in thinking. Without realizing it, of course, can cause a great psychological impact on the child that ultimately affects the mental and mental development of the child.